Hubungan Usia Dan Paritas Dengan Kejadian Perdarahan Postpartum Pada Ibu Bersalin Di RS PKU Muhammadiyah Gamping - Izza Syifa Wahyu Salfaira; Luluk Rosidah; Intan Mutiara Putri; Sri Ratnaningsih (Borneo Nursing Journal (BNJ), 2025)
Postpartum hemorrhage is the leading cause of maternal death worldwide with the incidence of 5%-10% of all deliveries. Bleeding is still a major problem in obstetrics today. Bleeding is the third leading cause of maternal death in both developed and developing countries, namely obstetric hemorrhage (27.03%). Approximately 14 million women worldwide suffer from postpartum hemorrhage each year, causing more than 70,000 maternal deaths. This study aims to determine the relationship between maternal age and parity and the incidence of postpartum hemorrhage in mothers giving birth at PKU Muhammadiyah Gamping Hospital. This study is a quantitative study with a cross-sectional approach. The sample of this study were 41 mothers giving birth at PKU Muhammadiyah Gamping Hospital which were selected by the quota technique sampling. The data source used was secondary data, namely medical records. Data analysis of the results the relationship between age and the incidence of postpartum hemorrhage shows that the results of the chi square test obtained a p-value = 0.02 or p < 0.05 with the results of OR = 14,625. Thus, Ha is accepted and Ho is rejected; which means there is a significant relationship between maternal age and the incidence of postpartum hemorrhage at PKU Muhammadiyah Gamping Hospital. The results of the chi square test obtained a p value = 0.08 or p < 0.05 with the results of OR = 7,464. Therefore, Ha is accepted and Ho is rejected; which means there is a significant relationship between maternal parity and the incidence of postpartum hemorrhage at PKU Muhammadiyah Gamping Hospital. So that the results obtained reveals that there is a relationship between age and parity and the incidence of postpartum hemorrhage. For postpartum mothers, it is expected that they have to consider the age and number of children in planning pregnancy at the right time. In addition, routine pregnancy check-ups with health workers should be carried out by the mother to detect the symptoms, so as to reduce the risk factors for bleeding and as a form of preventive efforts.